Fundamentals of sensor technology principles and novel designs - Altintas, Zeynep; Barhoum, Ahmed (Woodhead Publishing series in electronic and optical materials., 2023)
"Fundamentals of Sensor Technology: Principles and Novel Designs presents an important reference on the materials, platforms, characterization and fabrication methods used in the development of chemical sensor technologies. Sections provide the historical context of sensor technology development, review principles for the design of sensing devices and circuits, delve into the most common chemical and biological sensor types, cover unique properties and performance requirements, discuss fabrication techniques, including defining critical parameters, modeling and simulation strategies, and present important materials categories used in sensing applications, such as nanomaterials, quantum dots, magnetic materials, and more. This book is appropriate for the interdisciplinary community of researchers and practitioners interested in the development of sensor technologies, including materials scientists and engineers, analytical chemists and other related disciplines."